EKSPLORASI ETNOMATEMATIKA PADA TRADISI ADAT SESAJI REWANDHA JAWA TENGAH SEBAGAI KONTEKS PEMBELAJARAN UNTUK MENDUKUNG KEMAMPUAN NUMERASI SISWA - Nursyahidah, Farida; Wardono; Eko Susilo, Bambang (Universitas Cokroaminoto Palopo, 2024)
This research is an exploratory study to show the relationship between mathematics and culture. This study aims to explore the culture of the traditional activities of the Central Java Rewandha Sesaji tradition which contains mathematical concepts. This research uses ethnographic methods. Data collection techniques use ethnographic principles such as observation, interviews, documentation, and field notes with ethnographic descriptions. The results of the research show that in the traditional activities of the Central Java Rewandha Sesaji tradition there are several mathematical concepts, such as nets and the surface area of ​​a cylinder, the surface area of ​​a cone, the Pythagorean theorem, the area of ​​a circle, the circumference of a circle, parallel lines and quadrilaterals. Several mathematical concepts resulting from the exploration of these traditional traditions can then be used as context in learning to support students' numeracy skills. The results of this research can be used as inspiration for further research to explore other cultural traditions that can be used as a context for realistic mathematics learning that is more fun and meaningful.